Petrophysical Properties (Density and Magnetization) of Rocks from the Suhbaatar-Ulaanbaatar-Dalandzadgad Geophysical Profile in Mongolia and Their Implications - Tao Yang; Jintian Gao; Zuowen Gu; Baatarkhuu Dagva; Batsaikhan Tserenpil (The Scientific World Journal)
Petrophysical properties of 585 rock samples from the Suhbaatar-Ulaanbaatar-Dalandzadgad geophysical profile in Mongolia are presented. Based on the rock classifications and tectonic units, petrophysical parameters (bulk density, magnetic susceptibility, intensity of natural remanent magnetization, and Köenigsberger ratio) of these rocks are summarized. Results indicate that (1) significant density contrast of different rocks would result in variable gravity anomalies along the profile; (2) magnetic susceptibility and natural remanent magnetization of all rocks are variable, covering 5-6 orders of magnitude, which would make a variable induced magnetization and further links to complex magnetic anomalies in ground surface; (3) the distribution of rocks with different lithologies controls the pattern of lithospheric magnetic anomaly along the profile. The petrophysical database thus provides not only one of the keys to understand the geological history and structure of the profile, but also essential information for analysis and interpretation of the geophysical (e.g., magnetic and gravity) survey data.